Isolation and identification of heterotrophic bacteria with methane oxidation potential from various ecosystems as biological agents for reducing methane emissions - ERNI WIDIASTUTI; DWI ANDREAS SANTOSA; SYAIFUL ANWAR (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Widiastuti E, Santosa DA, Anwar S. 2026. Isolation and identification of heterotrophic bacteria with methane oxidation potential from various ecosystems as biological agents for reducing methane emissions. Biodiversitas 27 (4): d270423. https://doi.org/10.13057/biodiv/d270423. Methane is the second-largest greenhouse gas after carbon dioxide, contributing to global warming. Methane-oxidizing bacteria can help reduce methane emissions. However, the availability of methane-oxidizing bacteria isolated from various Indonesian ecosystems remains very limited, leaving a knowledge gap regarding their diversity and functional potential. This study aimed to isolate and identify bacteria from the swamp, river, and cattle manure ecosystems. Sediment samples were collected at 1-10 cm depth from five points in each ecosystem. Bacteria were isolated using a nitrate mineral salt medium supplemented with methane gas as a carbon source during incubation. The bacteria obtained were subjected to further analysis, namely morphological observation, pathogenicity testing through hypersensitivity and hemolysis analysis, indirect testing of Particulate Methane Monooxygenase (pMMO) and Soluble Methane Monooxygenase (sMMO) enzyme activity. Methane oxidation activity was quantified in three replicates for each isolate using gas chromatography. Molecular identification involved Polymerase Chain Reaction (PCR) amplifying the 16S rRNA gene. There are nine potential bacterial isolates with diverse morphological forms. In vitro tests show that all bacteria are non-pathogenic, with methanol production indirectly indicating pMMO enzyme activity, showing an average concentration of 1.80 mM, while sMMO activity is negative. The three best bacteria, Rw3, Rw4, and Sn1, had potential CH4 oxidation capabilities of 66.61, 62.39, and 62.55%, respectively, under laboratory conditions. The three bacteria were identified as Achromobacter sp., Exiguobacterium sp., and Burkholderia sp., with similarity values of 97.41%, 99.88%, and 98.85%, respectively. Although these three genera are not classified as methanotrophs, they exhibit potential methane-oxidizing activity under laboratory conditions. Overall, this study highlights the potential role of diverse heterotrophic bacterial genera in oxidizing methane, making them relevant biological candidates in the methane cycle.